Effect of Road Conditions on Vehicle Operation Costs on Roads in Kolaka Timur District - Nyoman Selvianti, Desak; Irwan Lakawa; Sitti Hawa (International Journal of Management and Education in Human Development, 2022)
The purpose of the study was to analyze the condition of street damage (SDI), analyze vehicle operating costs, and analyze the effect of street conditions on vehicle operating costs in the Welala – Ra-raa Street section. The research method uses an empirical approach and a statistical approach with data collection techniques carried out by direct measurements of street damage and vehicle travel speed. The analysis method for the level of road damage is the SDI method while the vehicle operational cost analysis method (BOK) uses the Lapi ITB method. The result of this study is that the damage to the wellala – ra-raa road is included in the category of heavily damaged with a surface distress index (SDI) of 387.9. vehicle operating costs (BOK) for motorcycles due to street damage is Rp 161.01 /km while the BOK for light vehicles is Rp 545.77 /km. the effect of street damage (SDI) on vehicle operating costs in the welala – ra-raa section is 0.001% for motorcycles while for light vehicles it is 8.9%.